Literasi Digital Sebagai Pilar Demokrasi Digital: Membangun Kesadaran Politik Masyarakat Di Era Disrupsi Teknologi - Cecep Nana Nasuha (Jurnal Ilmiah Muqoddimah: Jurnal Ilmu Sosial, Politik dan Hummaniora, 2025)
Digital technology development has fundamentally transformed Indonesia's political landscape. This research analyzes the role of digital literacy as a pillar of digital democracy in building public political awareness in the era of technological disruption. Indonesia's Digital Literacy Index in 2024 reached a score of 43.34, showing improvement from the previous year but still remaining in the moderate category. The research employs a literature review method by analyzing various academic sources related to digital literacy, digital democracy, and Indonesian public political participation. Findings reveal that low digital literacy contributes to the spread of misinformation and disinformation that threatens democratic integrity. Data shows that 42.3% of respondents still believe false information related to the 2024 Election, while 10.34% of political content on social media contains hate speech. This research concludes that structured and comprehensive digital literacy improvement is necessary to strengthen Indonesia's digital democracy through collaborative strategies among government, educational institutions, and civil society.